Kant e il punto di vista umano sullo spazio. Dall’Estetica trascendentale all’estetica come critica del gusto - Morawski, Tommaso (Aesthetica Preprint, 2023)
We can “speak of space, extended beings, and so on, only from the human standpoint”. So writes Kant in the Critique of Pure Reason at the conclusion of his (metaphysical and transcendental) exposition of the concept of space, emphasising that space and the relations that take place in it obtain “objective” meaning only when considered in accordance with the “laws of their conjunction”. Yet in nature, according to its a priori form, phenomena are treated without distinction of any kind, constituting, as Scaravelli wrote, a sensible texture that is “everywhere identical and perfectly isotropic”. Moreover, on the basis of transcendental principles of nature alone, what is different about individual phenomena cannot be justified. In the Critique of Pure Reason, this further dimension of knowledge was perceived as a problem and the question therefore remained open: how do we refer to the space in which sense objects find their place when we are not engaged in perceiving them in precise relations, as prescribed by the laws of the intellect to the transcendental synhypothesis of the imagination? What are the qualities of the representation of external objects when the human standpoint is not concerned with their cognitive presentation in an objective and analytically predetermined world? The aim of my paper is to shed light on these questions in order to investigate the representational modes of the external sense in those cases in which the cognitive presentation of external objects in an objective and analytically predetermined world is not at stake, but the mere conformity to subjective purposes of external intuitions. My proposal, in short, is to move out of the domain of nature in general and into the territory of particular experience, and explore what in spatial representation is simply subjective.